Dark personality and aggressiveness: The mediating role of anger and hostility - Thereza Lopes Ferreira, Nathane (2025)
Objective. This study aimed to verify the relationships between dark personality traits and the dimensions of aggressiveness. 208 individuals from the general population participated, with a mean age of 26.83 years (SD = 8.99). Method. The following measures were used: Dark Triad Dirty Dozen, Buss-Perry Aggression Questionnaire, and sociodemographic questionnaire. The data were explored using SPSS and JASP software. Results. The results showed that the dark personality traits narcissism, Machiavellianism and psychopathy were positively correlated with the four aggressiveness factors. Furthermore, dark personality traits showed direct and indirect effects, mediated by anger and hostility, on physical and verbal aggression. It is concluded that feelings (hostile) and emotion (anger) can contribute to the perpetuation of aggressive behaviors.